2016
DOI: 10.1021/acsami.6b10255
|View full text |Cite
|
Sign up to set email alerts
|

Cerenkov Radiation Induced Photodynamic Therapy Using Chlorin e6-Loaded Hollow Mesoporous Silica Nanoparticles

Abstract: Traditional photodynamic therapy (PDT) requires external light to activate photosensitizers for therapeutic purposes. However, the limited tissue penetration of light is still a major challenge for this method. To overcome this limitation, we report an optimized system that uses Cerenkov radiation for PDT by using radionuclides to activate a well-known photosensitizer (Chlorin e6, Ce6). By taking advantage of hollow mesoporous silica nanoparticles (HMSNs) that can intrinsically radiolabel oxophilic zirconium-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
113
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(119 citation statements)
references
References 36 publications
4
113
1
1
Order By: Relevance
“…(e) Co‐localization in vivo therapy results. (Reprinted with permission from Shaffer et al (), Kamkaew et al () and Kotagiri et al (). Copyright 2017, 2016 and 2018 American Chemical Society and Nature Publishing Group)…”
Section: Cherenkov Radiation‐induced Pdtmentioning
confidence: 99%
See 1 more Smart Citation
“…(e) Co‐localization in vivo therapy results. (Reprinted with permission from Shaffer et al (), Kamkaew et al () and Kotagiri et al (). Copyright 2017, 2016 and 2018 American Chemical Society and Nature Publishing Group)…”
Section: Cherenkov Radiation‐induced Pdtmentioning
confidence: 99%
“…Later, Thorek, Ogirala, Beattie, and Grimm (2013) studied Cherenkov radiation interacting with quantum dots for secondary Cherenkov-induced fluorescence imaging. Since that time several studies have reported that Cherenkov radiation can be exploited to activate PDT (Hartl, Hirschberg, Marcu, & Cherry, 2016;Kamkaew et al, 2016;Kotagiri, Sudlow, Akers, & Achilefu, 2015). Using Cherenkov radiation to induce PDT offers several potential advantages.…”
Section: Cherenkov Radiationmentioning
confidence: 99%
“…The nanoparticles, termed nanophotosensitizers, were targeted to tumours via transferrin attached to the surface, and the PDT from the combination of titanium dioxide and [ 18 F]-FDG showed a significant survival benefit compared with either of the agents alone. This work utilized the internal CL to photoactivate the nanoconstruct for oxidation-based therapy, for the first time liberating photodynamic therapy from the need of an external excitation source, similar to the internal excitation of fluorochromes 57 , with similar work using 89 Zr-nanoconstruct combinations also demonstrating therapeutic efficacy 58 . This approach is attractive due to the potential utilization of photodynamic therapeutics with clinical radiotracers already in routine use.…”
Section: Cerenkov-activatable Probes and Therapiesmentioning
confidence: 99%
“…Recently, CR was also used as a light source for chemical and therapeutic applications (14)(15)(16). In 2015, Kotagiri et al (15) demonstrated the use of CR generated by the 18 F-FDG radionuclide to activate TiO 2 nanoparticles in vivo to produce reactive oxygen species (ROS) and suppress the growth of cancer cells.…”
mentioning
confidence: 99%
“…It has a band gap of 3.2 eV and absorbs UV light efficiently-properties that match the high-intensity regimen of CR. Kamkaew et al (16) reported a system with a 89 Zr radionuclide (Cerenkov radiation source) and chlorin e6 (photocatalyst) and demonstrated its advantage in ROS generation through CR. Two radionuclides-68 Ga and 18 F-were recently studied for their cellular uptake and effectiveness in cancer treatment (23,24).…”
mentioning
confidence: 99%